Fate of Environmental Pollutants. (1st October 2017) - Kumar, Rahul; Sumaraj,; Padhye, Lokesh P.
Abstract : This annual review covers the literature published in 2016 on topics related to the occurrence and fate of emerging environmental pollutants in wastewater. Due to the vast amount of literature published on this topic, we have discussed only a portion of the quality research publications, due to limitation of space. The abstract search was carried out using Web of Science, and the abstracts were selected based on their relevance. In few cases, fulltext articles were referred to better understand new findings. This review is divided into the following sections: Antibiotic resistant bacteria (ARBs) and antibiotic resistant genes (ARGs), disinfection by‐products (DBPs), estrogens, nanomaterials, pathogens, perfluorinated chemicals (PFCs), pharmaceuticals and personal care products (PPCPs), and other pollutants.